Identification of Amino Acid Residues Required for the Substrate Specificity of Human and Mouse Chondroitin Sulfate Hydrolase (Conventional Hyaluronidase-4) - Kaneiwa, Tomoyuki (American Society for Biochemistry and Molecular Biology, 2012)
Human hyaluronidase-4 (hHYAL4), a member of the hyaluronidase family, has no hyaluronidase activity, but is a chondroitin sulfate (CS)-specific endo-β-N-acetylgalactosaminidase. The expression of hHYAL4 is not ubiquitous but restricted to placenta, skeletal muscle, and testis, suggesting that hHYAL4 is not involved in the systemic catabolism of CS, but rather has specific functions in particular organs or tissues. To elucidate the function of hyaluronidase-4 in vivo, mouse hyaluronidase-4 (mHyal4) was characterized. mHyal4 was also demonstrated to be a CS-specific endo-β-N-acetylgalactosaminidase. However, mHyal4 and hHYAL4 differed in the sulfate groups they recognized. Although hHYAL4 strongly preferred GlcUA(2-O-sulfate)-GalNAc(6-O-sulfate)-containing sequences typical in CS-D, where GlcUA represents d-glucuronic acid, mHyal4 depolymerized various CS isoforms to a similar extent, suggesting broad substrate specificity. To identify the amino acid residues responsible for this difference, a series of human/mouse HYAL4 chimeric proteins and HYAL4 point mutants were generated, and their preference for substrates was investigated. A combination of the amino acid residues at 261–265 and glutamine at 305 was demonstrated to be essential for the enzymatic activity as well as substrate specificity of mHyal4.